Motivation for participation or non-participation in group tasks: A dynamic systems model of task-situated willingness to communicate. (June 2015) - Eddy-U, Mary
Abstract: The effectiveness of group tasks in L2 classes relies in large part on individual students' Willingness to Communicate (WTC) during the duration of the task. Dörnyei (2009) suggested four conglomerates of task motivation from a dynamic systems perspective, but these conglomerates may not include all possible factors affecting task-situated WTC. Focus group based research was used to explore what English language learners at two universities in Macau, a Special Administrative Region of China, say motivates them to participate or not participate in group tasks. Interest, perceived effectiveness, good groupmates, good classroom social situation, personal vision and self-confidence were themes identified as both motivating and also, when in inverse form or absent in student experience, demotivating. Marks were also identified as a motivating influence. Overall, Macau students mentioned that social factors and task-related factors significantly influenced task-situated WTC in addition to self-confidence and L2 learning motivation, which are part of general L2 WTC models. In light of these findings, recommendations are made to adjust and add to Dörnyei's (2009) conglomerates to create a model of task-situated WTC. Some suggestions for further research and implications for L2 teachers in arranging group tasks are given.